TINGKAT KOGNISI ANAK INDONESIA BERUSIA 5,5-12,0 TAHUN: HASIL SEANUTS DI INDONESIA - Nurmeida S Syarief; Basuki Budiman; nFN Sandjaja (GIZI INDONESIA, 2013)
Perkembangan kognisi atau karakteristik mental dicirikan dengan perkembangan persepsi, memori, imajinasi, daya pikir, kecerdasan. Artikel ini menyajikan hasil SEANUTS tentang tingkat kognisi anak berusia 5,5-12,0 tahun secara deskriptif. Partisipan sebanyak 1368 menggambarkan populasi nasional yang diambil secara acak jamak bertingkat (two stage randomized cluster sampling). Raven’s Coloured Progressive Matrices (CPM) digunakan untuk mengukur tingkat kognisi anak. Kelompok anak terdiri 5,5-7,9 tahun dan 8,0-12,0 tahun. Tingkat kognisi disajikan menurut postur tubuh. Postur dinilai dari skor Z pada indeks TB/U. Tingkat kognisi di bawah rerata pada anak kelompok berusia 5,5-7,9 tahun antara 16,0- 50,0 persen; dan kelompok berusia 8,0-12,0 tahun antara 25,7-69,6 persen. Secara keseluruhan, asosiasi antara kognisi dan postur tubuh tidak nyata pada anak berusia 5,5-7,9 tahun. Pada kelompok usia yang lebih tua tampak perbedaan yang signifikan baik di perkotaan maupun di perdesaan (p0,05). Namun demikian, hubungan itu diduga dipengaruhi oleh lingkungan tempat anak tumbuh termasuk stimulasi neuropsikologis dan status gizi baik mikro maupun makroABSTRACT COGNITIVE LEVEL OF CHILDREN 5.5-12.0 YEARS OLD: RESULT OF SEANUTS IN INDONESIA Cognitive or mental characteristic development includes development of perception, memory, imagination, intellectual skill and IQ. This article provides SEANUTS’ result especially on mental development of school children (5.5-12.0 years old). A nationally representative number of 1368 children involved in this study. Two-stage randomized cluster sampling was implied for deriving required participants. Raven’s Coloured Progressive Matrices (CPM) was administered to measure cognition. Posture was represented by HAZ score. Results showed that proportion of level cognition was below average in the 5.5-7.9 year age group and in the 8.0-12.0 year age group between 16.0- 50.0 percent and 25.7-69.6 percent respectively. The association between cognition and posture at younger group was unclear while at older group, it seemed significantly different (p0.05) both in rural and urban. However, the significant association at lower cognition level were influenced by environment where chlidren grow including neuropsychological stimulation and nutritional status both micro- and macronutrient level. Keywords: cognition, posture, CPM, Indonesian children